Impact of health insurance equity on poverty vulnerability: evidence from urban–rural health insurance integration in rural China - Li, Zhipeng; Chen, Yuqian; Ding, Jing (Frontiers in Public Health, 2023)
Background: In 2016, the Chinese government introduced an integration reform of the health insurance system with the aim to enhance equity in healthcare coverage and reduce disparities between urban and rural sectors. The gradual introduction of the policy integrating urban and rural medical insurance in pilot cities provides an opportunity to evaluate the policy impact. This study attempts to assess the policy impact of urban-rural health insurance integration on the chronic poverty of rural residents and to analyze the mechanisms. Method: Based on the 4 waves of data from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2011, 2013, 2015, and 2018, we employ a staggered difference-in-differences (staggered DID) model to assess the impact of integrating urban-rural health insurance on poverty vulnerability among rural inhabitants, and the mediation model to analyze the mechanism channel of the policy impact. Results: (1) Baseline regression analysis revealed that the urban-rural health insurance integration significantly reduces 6.32% (p<0.01) the poverty vulnerability of rural residents. One health insurance system with one unified scheme of contribution and Benefits package (i.e., OSOS, 6.27%, p<0.01) is more effective than the transitional one health insurance system with multiple schemes (i.e., OSMS, 3.25%, p<0.01). (2) The heterogeneity analysis results show that the urban-rural health insurance integration had a more significant impact on vulnerable groups with relatively poor health (7.84%, p<0.1) than those with fairly good health (6.07%, p<0.01), and also significantly reduce the poverty vulnerability of the group with chronic diseases by 9.59% (p<0.01). The integration policy can significantly reduce the poverty vulnerability of the low consumption and low medical expenditure groups by (8.6%, p<0.01; 7.64%, p<0.01) respectively, compared to their counterparts. (4) The mechanism analysis results show that the urban-rural health insurance integration can partially enhance labor supply (14.23%, p<0.01) and physical examination (6.28%, p<0.01). The indirect effect is between the integration policy and poverty vulnerability through labor supply and physical examination are 0.14%, 0.13% respectively.